Immunophenotype associated with high sustained antibody titers against enzyme replacement therapy in infantile-onset Pompe disease - Desai, Ankit K.; Smith, P. Brian; Yi, John S.; Rosenberg, Amy S.; Burt, Trevor D.; Kishnani, Priya S. (Frontiers in Immunology, 2024)
The efficacy of enzyme replacement therapy (ERT) with alglucosidase alfa for infantile-onset Pompe disease (IOPD) is limited in some patients due to the development of high and sustained antibody titers (HSAT; ≥12,800). We carried out detailed immunophenotyping of IOPD patients (n=40), including analysis of circulating cell populations by flow cytometry and plasma cytokines by multiplex array, to determine whether patients with HSAT have unique immunological characteristics compared to those with low titers (LT; <12,800). Compared to patients with LT, patients who develop HSAT were skewed toward a type 2 immune profile, with an increased frequency of Th2 cells that was positively correlated with levels of Th2 (IL-4, IL-5, IL-13) and pro-inflammatory (IL-6, TNF-, MIP-1, MIP-1) cytokines. B cells were increased in HSAT patients with a decreased fraction of unswitched memory B cells. Plasma GM-CSF concentrations were lower on average in HSAT patients, while CXCL11 was elevated. Finally, using principal components analysis, we derived an HSAT Signature Score that successfully stratified patients according to their antibody titers. The immune profiles revealed in this study not only identify potential biomarkers of patients that developed HSAT but also provide insights into the pathophysiology of HSAT that will ultimately lead to improved immunotherapy strategies.